Existence of global solutions to nonlinear mixed-type functional differential equations. (June 2020) - Diblík, J.; Vážanová, G.
Abstract: The paper considers systems of nonlinear mixed-type functional differential equations. It aims to find conditions for the existence of global solutions with graphs staying in a prescribed domain. A relevant result is proved by Schauder–Tychonoff fixed-point technique with illustrative examples shown. A linear variant of the derived result is formulated, comparisons with known results are discussed and some open problems are formulated.